Viruses, Vaccines, and COVID-19: Explaining and Improving Risky Decision-making - Reyna, Valerie F.; Broniatowski, David A.; Edelson, Sarah M. (Journal of applied research in memory and cognition, 2021)
Risky decision-making lies at the center of the COVID-19 pandemic and will determine future viral outbreaks. Therefore, a critical evaluation of major explanations of such decision-making is of acute practical importance. We review the underlying mechanisms and predictions offered by expectancy-value and dual-process theories. We then highlight how fuzzy-trace theory builds on these approaches and provides further insight into how knowledge, emotions, values, and metacognitive inhibition influence risky decision-making through its unique mental representational architecture (i.e., parallel verbatim and gist representations of information). We discuss how social values relate to decision-making according to fuzzy-trace theory, including how categorical gist representations cue core values. Although gist often supports health-promoting behaviors such as vaccination, social distancing, and mask-wearing, why this is not always the case as with status-quo gist is explained, and suggestions are offered for how to overcome the "battle for the gist" as it plays out in social media. General Audience Summary Throughout the COVID-19 pandemic, risky decision-making has determined its trajectory, from deciding whether to socially distance or wear a mask to whether to get vaccinated. Major theories of risky decision-making make different predictions about COVID-19, discussed in this article. According to expectancy-value theories, decisions are made based on relative risks and benefits, suggesting that interventions aiming to reduce risky decisions should focus on making sure people have objectively accurate perceptions about risks, often through providing detailed information. Dual-process theories emphasize two systems that govern decision-making: one unconscious and automatic, the other controlled and deliberative. According to both groups of theories, greater reflection or deliberation is expected to reduce risk taking related to COVID-19. Fuzzy-Trace Theory (FTT) emphasizes that multiple mental representations of information ranging from those that capture precise verbatim details to those that emphasize the underlying meaning, or gist, are encoded and processed separately in parallel. However, gist representations are more durable than verbatim representations and so influence decisions more. Gist can support either risk aversion or risk seeking depending on how decisions are framed and how the status quo is perceived (i.e., as categorically "okay" or "not okay"). Crucially, whether social norms or values influence a decision depends on people's mental representation of their situation. Because young people are major vectors of COVID-19, developmental implications are discussed, and while some theories make bleak predictions about young people's abilities to prevent the spread of COVID-19, FTT suggests that support in developing the right gist can help them avoid dangerous risks, especially when paired with strong prosocial values and norms. We close by highlighting how many of these themes play out in social media, where messages that are more gisty tend to be more widely shared regardless of whether they contain misinformation, and how providing accurate information is not a sufficient remedy by itself. According to FTT, when trusted sources provide accurate, boiled-down, and meaningful messages emphasizing key information about COVID-19, people are more likely to share such messages and have a better chance of making decisions in accordance with their values.